Factors shaping the decision to become a landlord and retain rental investments - Wood, G.; Ong, Rachel (Australian Housing and Urban Research Institute (AHURI), 2010)
The supply of private rental housing has become more prominent in the debates around affordable housing as house prices have increasingly gotten out of the reach of prospective home owners, and rents have spiralled in rental housing. There is a concern that private rental markets are failing on the supply side due to principal-agent problems, taxation measures and regulations. In this project, we explore the role of different variables in shaping the supply decisions of private rental investors. This exploration will shed insights on how policy initiatives such as tax measures will impact on the economic costs of landlords, and how this will in turn affect their propensity to hold onto property investments.